Caribou nursery site habitat characteristics in two northern Ontario parks - Carr, Natasha L.; Rodgers, Arthur R.; Walshe, Shannon C. (Rangifer, 2007)
To prevent further range recession, habitat features essential to the life-history requisites of woodland caribou (Rangifer tarandus caribou) such as calving and nursery sites need to be protected for the persistence of the species. Woodland caribou may minimize predation risk during calving by either spacing out or spacing away from predators in the forest to calve on islands, wetlands, or shorelines. Our objective was to determine the characteristics of shoreline habitats used as calving and nursery sites by female woodland caribou in northern Ontario. Detailed vegetation and other site characteristics were measured at nursery sites used by cow-calf pairs in Wabakimi and Woodland Caribou Provincial Parks for comparison with shoreline sites that were not used by caribou within each park. Differences in habitat variables selected by female caribou in the two study areas reflect broad ecoregional differences in vegetation and topography. In Wabakimi Provincial Park, understorey tree density and ground detection distance played key roles in distinguishing nursery sites from sites that were not used. In Woodland Caribou Provincial Park, groundcover vegetation and shrub density were important in the selection of nursery sites by female caribou. Generally, female caribou in both parks selected nursery sites with greater slope, lower shrub density but thicker groundcover vegetation, including greater lichen abundance, and higher densities of mature trees than shoreline sites that were not used. The identification of these important features for caribou nursery sites provides a basis for improving their protection in future management policies and legislation.